The migratory imagination: Anna Funder's Stasiland as prosthetic memory. Issue 1 (1st April 2013) - Mitchell, Kate
The generic status of Anna Funder's Stasiland (2002) is uncertain, but it is clear from the opening pages that the author conceptualizes her project as an act of memory: it is an attempt to document a past that ended abruptly in 1989 with the dissolution of the German Democratic Republic and which, she perceives, many are eager to forget. As an Australian writer revisiting German history, she thus attempts to recuperate a past that does not 'belong' to her. But how can one remember a past that is not one's own? Can we presume to speak on another nation's behalf, to imagine another country's traumatic history? And how might 'creative nonfiction' perform cultural memory in this way? This article examines Stasiland's status as an example of Alison Landsberg's notion of 'prosthetic memory' (2004), which fosters an affective connection to a mediated foreign past. I argue that in Stasiland, Funder deploys a range of literary strategies to make the past both comprehensible and memorable for her foreign readers, creating a community of memory across borders